All Days 2011
DOI: 10.2118/149512-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Stress and Formation Properties on the Outcome of Fracture Operations in Horizontal Shale Wells

Abstract: The natural gas production is gaining importance as a clean source of energy. Several potential sources exist for gas production in the Appalachian Basin with the Marcellus shale being the largest resource in the U.S. This covers several states in the Eastern U.S. and plays a vital role in the future of gas production. As a result operators are interested in the development of the shale resources mostly with multi-stage fractures using a horizontal well. However, the lack of commercially available information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…This drilling method exposes the wellbore to a greater surface area of the target formation than traditional vertical drilling, as shown in In a recent study by Bilgesu and Yusuf (2011), simulations were performed to investigate the influence of formation stress levels in various shale formations on the outcome of fracture treatments when the formation contains discrete natural fractures. This study showed that the horizontal stresses which exist in an area can alter the shape and size of a fracture treatment (Bilgesu & Yusuf, 2011). It was also found that gas production in shale formations can increase with an increased stress difference between layers.…”
Section: Purposes Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…This drilling method exposes the wellbore to a greater surface area of the target formation than traditional vertical drilling, as shown in In a recent study by Bilgesu and Yusuf (2011), simulations were performed to investigate the influence of formation stress levels in various shale formations on the outcome of fracture treatments when the formation contains discrete natural fractures. This study showed that the horizontal stresses which exist in an area can alter the shape and size of a fracture treatment (Bilgesu & Yusuf, 2011). It was also found that gas production in shale formations can increase with an increased stress difference between layers.…”
Section: Purposes Introductionmentioning
confidence: 76%
“…It was also found that gas production in shale formations can increase with an increased stress difference between layers. This was insignificant for a single fracture treatment, but can be an important economic factor in multi-stage treatments (Bilgesu & Yusuf, 2011 This can help in achieving maximum attainable injection rates to effectively transmit the fracturing pressure from the wellbore to the formation, and thus maximize reservoir stimulation.…”
Section: Purposes Introductionmentioning
confidence: 99%
“…Also, secondary fracture volume and length were compared to study the effect on the Discrete Fracture Network (DFN) and they noticed that there is an increase in the fracture half-length and fracture volume with the increase of the horizontal stress level; however, there is a decrease in the secondary fracture half-length but there is an increase in stimulated reservoir area. This was clearly indicated on the production output because the production increased with the increase in the horizontal stress level (39) .…”
Section: Previous Workmentioning
confidence: 89%
“…Bilgesu and Yusuf (39) conducted research to study the impact of stress and formation properties on the outcome of fracture in horizontal shale well. This study performed with Marcellus shale data to basically study the effects of variations in horizontal stress levels on the fracture geometry and properties and also understand their impact on the production from horizontal shale wells.…”
Section: Previous Workmentioning
confidence: 99%
“…This stress field may be defined by three principal stresses, which are oriented perpendicular to each other. The magnitudes and orientations of these three principal stresses are determined by the tectonic regime in the area and by depth, pore pressure and rock properties, which regulate how stress is carried and distributed among formations (Bilgesu et al, 2011). In situ stresses control the orientation and propagation direction The three principal stresses increase with depth.…”
Section: Three Principle Stressesmentioning
confidence: 99%